2013
DOI: 10.3947/ic.2013.45.1.62
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Arbekacin and Vancomycin for the Treatment in Skin and Soft Tissue MRSA Infection: Preliminary Study

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) has become a one of the most important causes of nosocomial infections, and use of vancomycin for the treatment of MRSA infection has increased. Unfortunately, vancomycin-resistant enterococcus have been reported, as well as vancomycin-resistant S. aureus. Arbekacin is an antibacterial agent and belongs to the aminoglycoside family of antibiotics. It was introduced to treat MRSA infection. We studied the clinical and bacteriological efficacy and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Investigating further, we conducted a study of skin and soft tissue infections due to MRSA. The results of that study with regard to the clinical and bacteriological efficacy were not different between the two groups; however, adverse reactions were less commonly reported in the arbekacin group ( 30 ).…”
Section: Discussionmentioning
confidence: 83%
“…Investigating further, we conducted a study of skin and soft tissue infections due to MRSA. The results of that study with regard to the clinical and bacteriological efficacy were not different between the two groups; however, adverse reactions were less commonly reported in the arbekacin group ( 30 ).…”
Section: Discussionmentioning
confidence: 83%
“…Recently arbekacin was found to be a safe and effective alternative to vancomycin to treat S. aureus infections [15]. These data prove the efficacy of aminoglycosides against S. aureus but monotherapy is not a commonplace.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on clinical efficacy, bacteriological efficacy, and safety against MRSA infection which compared the treatment of VCM and ABK. 49 , 50 Hwang et al 50 reported that the bacteriological efficacy responses of ABK and VCM were 71.2% and 79.5%, respectively, and the clinical efficacy responses of those were 65.3% and 76.1%, respectively, and that there was no statistically significant difference between ABK and VCM. The incidence of complications was significantly higher in the VCM group (32.9%) in comparison with the ABK group (15.1%) ( P =0.019).…”
Section: Clinical Efficacymentioning
confidence: 99%